Self micro‑emulsifying drug delivery system of tacrolimus: Formulation, in vitro evaluation and stability studies - V Patel, Pranav; K Patel, Hitesh; S Panchal, Shital; A Mehta, Tejal (International Journal of Pharmaceutical Investigation, 2013)
Background: Tacrolimus has poor solubility in water ranging from 4 to 12 µg/mL. The oral bio availabilities of tacrolimus is poor and exhibits high intra and inter‑subject variability (4‑89%, average 25%) in the liver and the kidney transplant recipients and in patients with renal impairment. Aim: The present study deals with the development and characterization of self‑micro‑emulsifying drug delivery system to improve the oral bioavailability of poorly soluble drug tacrolimus. Materials and Methods: Solubility of the tacrolimus was estimated in various oils, surfactants, and co‑surfactants. Various in vitro tests such as percentage transmittance, emulsification time, cloud point, precipitation, and thermodynamic stabilities were used to find out optimized formulations. Optimized liquid self micro‑emulsifying (SMEDDS) were characterized by particle size analysis and converted in solid by using the Florite RE as an adsorbent, which is further characterized by differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X‑ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and particle size analysis. Results: The optimized liquid SMEDDS formulation contained 10% Lauroglycol FCC as an oil, 60% Cremophor RH, and 30% PEG (polyethylene glycol) 400 as a surfactant and co‑surfactant respectively. The optimized liquid and solid SMEDDS showed higher drug release than the marketed capsule and pure API (active pharmaceutical ingredient) powder. For optimized liquid SMEDDS and solid SMEDDS, the globule sizes were found 113 nm and 209 nm respectively. The solid state characterization of solid‑SMEDDS by SEM, DSC, FTIR, and XRD revealed the absence of crystalline tacrolimus in the solid‑SMEDDS. Shelf‑lives for liquid SMEDDS and solid SMEDDS were found to be 1.84 and 2.25 year respectively. Conclusions: The results indicate that liquid SMEDDS and solid SMEDDS of tacrolimus, owing to nano‑sized, have potential to enhance the absorption of the drug.
Keywords: Cremophor RH; lauroglycol FCC; solid SMEDDS; tacrolimus